1992
DOI: 10.1007/bf01317141
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide sequence of the coat protein gene and 3? untranslated region of papaya ringspot virus type W (Aust)

Abstract: The nucleotide sequence of the 3' terminal region of the Australian isolate of papaya ringspot virus type W [PRSV-W (Aust)] was determined. An open reading frame (864 bp), encoding the putative coat protein gene, occurs upstream of the putative 3' untranslated region (206 bp) and poly(A) tail. A 23 amino acid sequence was obtained from N-terminal analysis of the coat protein from purified virions. This sequence has 100% homology with a region of the amino acid sequence inferred from the nucleic acid sequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Initially, information from the coat protein gene sequences of PRSV-W and PRSV-P from the U.S.A. (Quemada et al, 1990;Wang & Yeh, 1992) and PRSV-W from Australia (Bateson & Dale, 1992) suggested that there was very little sequence variability within this gene between isolates of PRSV. However, in this study we have found considerable variability in coat protein gene sequences of PRSV from different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, information from the coat protein gene sequences of PRSV-W and PRSV-P from the U.S.A. (Quemada et al, 1990;Wang & Yeh, 1992) and PRSV-W from Australia (Bateson & Dale, 1992) suggested that there was very little sequence variability within this gene between isolates of PRSV. However, in this study we have found considerable variability in coat protein gene sequences of PRSV from different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the sequence of the coat protein gene of DB 1, an Australian glasshouse isolate of PRSV-W (Bateson & Dale, 1992) and showed that there was considerable nucleotide (at least 96%) and amino acid (at least 98 %) sequence similarity with U.S. isolates of PRSV-P and W (Quemada et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…These two sites may be functional; the upstream site for producing a functional Nib protein, and the other, to produce an aphid-transmissible coat protein. Nucleotide sequences have been reported for the coat protein genes of 16 PRSV-p and PRSV-w types from different geographic regions (2,3,41,(55)(56)(57)65). It is impossible to segregate PRSV-p and PRSV-w types by their coat protein sequences.…”
Section: Papaya Ringspot Virusmentioning
confidence: 99%
“…The sponge gourd Cuban isolate clustered together with a Momordica charantia Cuban PRSV-W isolate (GenBank accession number KP019380) (Cabrera Mederos et al 2015), and other PRSV-W isolates from United States of America (Abdalla and Ali 2012), Australia and Venezuela (Bateson and Dale 1992;Romay et al 2014b). However, the Cuban PRSV-W isolate of Cucurbita pepo was found to be grouped with the Brazilian PRSV-W isolates.…”
mentioning
confidence: 99%